Cochlear Marginal Cell Pyroptosis Is Induced by Cisplatin via NLRP3 Inflammasome Activation - Yu, Wenting; Zong, Shimin; Zhou, Peng; Wei, Jiahui; Wang, Enhao; Ming, Ruijie; Xiao, Hongjun (Frontiers in Immunology, 2022)
Better understanding the mechanism of cisplatin-induced ototoxicity is of great significance for clinical prevention and treatment of cisplatin related hearing loss. However, the mechanism of cisplatin-induced inflammatory response in cochlear stria vascularis and the mechanism of marginal cell (MC) damage have not been fully clarified. In this study, a stable model of cisplatin-induced MCs damage was established in vitro, and the results of PCR and western blotting showed increased expressions of NLRP3, Caspase-1, IL-1β, and GSDMD in MCs. Incomplete cell membranes including many small pores appearing on the membrane were also observed under transmission electron microscopy and scanning electron microscopy. In addition, down-regulation of NLRP3 by small interfering RNA can alleviate cisplatin-induced MCs pyroptosis, and reducing the expression level of TXNIP possess the inhibition effect on NLRP3 inflammasome activation and its mediated pyroptosis. Taken together, our results suggest that NLRP3 inflammasome activation may mediate cisplatin-induced MCs pyroptosis in cochlear stria vascularis, and TXNIP is a possible upstream regulator, which may be a promising therapeutic target for alleviating cisplatin-induced hearing loss.